Kinerja Pemasaran Agribisnis Kakao Dalam Mendukung Kesejahteraan Petani di Kabupaten Kolaka - Masitah, Masitah; Hasbiadi, Hasbiadi; Rahmawati, Rahmawati; Rendi, Rendi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
One of the largest cocoa producing areas in Southeast Sulawesi is Kolaka Regency, which makes cocoa one of the leading commodities cultivated by farmers. Problems with the cocoa commodity in Kolaka Regency include plant productivity which is still low which results in the selling value of cocoa decreasing. Farmers' income in farming is closely related to welfare. Apart from the farming system, marketing is also an important thing that needs to be considered in increasing farmers' income. The urgency of this research can be used as a consideration for the government in making policies related to the development of the cocoa commodity in Kolaka Regency so that it can develop the agricultural sector, especially improving the welfare of cocoa farmers. This research is a form of effort to strengthen sustainable agriculture in Kolaka Regency. The research method used was a survey method of drawing farmers as samples which was carried out proportionally by random sampling of nine respondents and there were two cocoa trader respondents. The analysis in this research includes farmer share analysis, marketing channel analysis, sales margin analysis of product forms. The results of the research show that there are three channels for marketing cocoa plants in Kolaka Regency, namely the first channel from farmers then to local traders then to companies, the second channel from farmers then to local traders, to foreign traders and then sold to companies, while the second channel is from the third marketing is from farmers directly selling to companies. With the results of farmer share in the three marketing channels in Kolaka Regency, it is already efficient. And channel III is the most efficient marketing channel because there is no long marketing channel chain.